Cell-specific targeted nanosystem to modulate the tumour microenvironment - Dias, Sofia Catarina Ponce (2023)
Cancer treatments remain strongly reliant on conventional therapies that have limited efficacy as well as cytotoxic side-effects on off-target healthy cells. Immunotherapy presents a promising approach for training the host’s immune system to fight the tumour. However, currently approved immunotherapeutic treatments are hampered particularly by low response rates and autoimmune responses, despite their potential in case of full response. Further investigating and improving the actuation of this therapeutic approach would contribute to future oncologic treatment options. The tumour microenvironment plays a pivotal role in carcinogenesis, dynamically changing to provide the tumour with the appropriate conditions for progression. Macrophages in the tumour microenvironment pose as a particularly promising target for immunotherapy, as their tumour-induced immunosuppressive behaviour can be reprogrammed towards tumour-hostile activity through their repolarization into M1 macrophages. Targeting macrophages for cancer therapy to activate the immune system is possible through the use of a nanocarrier to target the desired cells and deliver the therapeutic agent, such as nucleic acids. In this work, the main goal was to develop a novel lipid nanocarrier for the targeted delivery of mRNA to activated macrophages. For this, cationic liposomes, containing in their formulation a targeting lipid to provide the cell-specific delivery to macrophages, were synthetized, loaded with eGFP- or luciferase-encoding mRNA and characterized for their size, polydispersity index, zeta potential and encapsulation efficiency through Dynamic Light Scattering and spectrophotometry. Their effects on the macrophage RAW 264.7 cell line were examined through fluorescent microscopy, flow cytometry, luminescence detection, and their metabolic activity was assessed with an Alamar Blue assay. These steps were followed also for a formulation of liposomes without the TL to test the targeting ability of the nanoparticles. The obtained liposomes possessed a size of approximately 130 nm for the unloaded nanoparticles, with an increase in size with loading for micrometre-range dimensions. Their zeta potential ranged from 52 – 57 mV in the unloaded particles, varying then with their loading with RNA. The lipoplexes successfully transfected RAW 264.7 macrophages and induced the production of the intended proteins. Nevertheless, their targeting ability towards macrophages, compared to tumour cells, still requires further investigation.